Wawasan Al-Qur’an tentang Estetika - Abdur Rokhim Hasan (LP2M Universitas PTIQ Jakarta, 2016)
The Qur’an contains many outstanding aesthetics, that few people were able to reveal this beauty. Such an attractions as the beauty of the Qur’an are scientific and non-scientific, namely faith and transcendental, so humans could reveal scientific beauty of the Qur’ran, but few are able to reveal the beauty of faith and transcendental. Uncovering and enjoying the beauty of Qur’an as well as uncovering and enjoying the beauty of Allah, Himself, as the Owner of the Qur’ran. Because Allah is the most beautiful one, so that His beauty is reflected in all of His word, which covers all aspects of life. The Qur’an contains beauty in writing and reading. The Qur’an also reveals the natural beauty of the universe with a wide variety of forms, stretching from the planets (Earth, sun, moon, stars), flora and fauna up to humans. The Qur’an also reveal the values of beauty, moral values, virtues, and expectations. Even the beauty of heaven revealed by al-Qur’an was the inspiration the beauty of human life.